Is it feasible to involve parents of teenagers with ASD in their language teaching? A case study in Greece - Kotsi, Despina; Fernández Robles, Bárbara (Technium Social Sciences Journal, 2023)
Autism spectrum disorder (ASD) as a lifelong neurodevelopmental disorder puts a significant strain on the family. During secondary education, when the brain is rewired, language learning becomes a challenge for ASD students and their parents. Using this as a foundation, this article’s main objective is to know the opinions and attitudes that characterize the parents of adolescents with ASD regarding the teaching of the Greek language to their children. Through a descriptive qualitative study, with a semi-structured interview of 32 items (n=30 parents) and an in-depth analysis, this goal has been accomplished. The main conclusion that has been reached is that participants-parents applaud their own assistance in the educational process, claiming though for special education teachers’ cooperation, support from the Greek State and availability of specialized staff and resources to carry out smoothly the language learning process, with the aim of optimal outcomes in the linguistic competencies for their ASD adolescents.